Preparation, Characterization and Stability Studies of Gold Nanoparticles Capped by 1, 2, 3‐Triazole‐Based Mesoionic Carbenes. Issue 34 (8th September 2022) - Cui, Liu; Du, Mingwei; Guo, Shuai
Abstract: The preparation of stable and size‐uniform AuNPs (AuNPs=gold nanoparticles) has gained extensive attention. Strongly coordinating 1, 2, 3‐triazole‐based mesoionic carbenes are suitable capping agents to stabilize AuNPs, but such chemistry has been rarely explored. In this work, a series of newly synthesized triazolin‐5‐ylidenes with varying wingtips have been exploited as the capping ligands. Two different synthetic approaches have been explored and compared, which employed either gold(I) complexes or gold(III) species as the precursors. The gold nanomaterials synthesized via these two routes show different characteristics in terms of particle size, surface oxidation state as well as colloidal stability. It was found that the carbene with two long aliphatic wingtips is the best capping ligand giving relatively stable and monodisperse AuNPs. In addition, one of the gold nanomaterials, NP‐IIc, has exhibited good stability in the presence of biologically relevant agents including PBS, cysteine and glutathione, which implies its potential biological applications. Abstract : Gold nanoparticles capped by mesoionic triazole‐based carbenes have been synthesized using either well‐defined gold(I) carbene complexes or triazolium tetrachloroaurate(III) as the precursors. The spectroscopic characteristics, microscopic features and colloidal stability of the as‐synthesized AuNPs have been reported.